Cognitive and Behavioral Impairments Evoked by Low-Level Exposure to Tobacco Smoke Components: Comparison with Nicotine Alone - Hall, Brandon J. (Toxicol Sci, 2016)
Active maternal smoking has adverse effects on neurobehavioral development of the offspring, with nicotine (Nic) providing much of the underlying causative mechanism. To determine whether the lower exposures caused by second-hand smoke are deleterious, we administered tobacco smoke extract (TSE) to pregnant rats starting preconception and continued through the second postnatal week, corresponding to all 3 trimesters of fetal brain development. Dosing was adjusted to produce maternal plasma Nic concentrations encountered with second-hand smoke, an order of magnitude below those seen in active smokers. We then compared TSE effects to those of an equivalent dose of Nic alone, and to a 10-fold higher Nic dose. Gestational exposure to TSE and Nic significantly disrupted cognitive and behavioral function in behavioral tests given during adolescence and adulthood (postnatal weeks 4–40), producing hyperactivity, working memory deficits, and impairments in emotional processing, even at the low exposure levels corresponding to second-hand smoke. Although TSE effects were highly correlated with those of Nic, the effects of TSE were much larger than could be attributed to just the Nic in the mixture. Indeed, TSE effects more closely resembled those of the 10-fold higher Nic levels, but still exceeded their magnitude. In combination with our earlier findings, this study thus completes the chain of causation to prove that second-hand smoke exposure causes neurodevelopmental deficits, originating in disruption of neurodifferentiation, leading to miswiring of neuronal circuits, and as shown here, culminating in behavioral dysfunction. As low level exposure to Nic alone produced neurobehavioral teratology, ‘harm reduction’ Nic products do not abolish the potential for neurodevelopmental damage.